2017
DOI: 10.5455/medarh.2017.71.32-36
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Subjective Symptoms in Patients with Benign Prostatic Hyperplasia and Erectile Dysfunction

Abstract: Introduction:Epidemiological studies suggest a link between the symptoms of lower urinary tract (LUTS) caused by benign prostatic hyperplasia (BPH) and erectile dysfunction (ED). Increasing expected period of life, justify the interest of establishing correlations LUTS / BPH and ED in order to find more efficient ways of treating these pathologies.Goal:The objective was to evaluate the correlation of symptoms in LUTS/BPH with the degree of ED.Patients and Methods:The study was conducted as a prospective study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…Several studies have shown that DM-2 is associated with a significantly low serum total PSA level than in non-diabetic individuals due to lower androgen levels found in diabetic men ( 2 ). Likewise, another study by Muller et al ( 3 , 4 ) reported that men with very high level of hemoglobin A1c (like in our patient) had 29% lower serum levels of PSA at later stages of diabetes. There have been additional reports on the decrease in testosterone level in men with DM-2 due to hypogonadism evident with low PSA values ( 4 ).…”
Section: Discussionsupporting
confidence: 82%
“…Several studies have shown that DM-2 is associated with a significantly low serum total PSA level than in non-diabetic individuals due to lower androgen levels found in diabetic men ( 2 ). Likewise, another study by Muller et al ( 3 , 4 ) reported that men with very high level of hemoglobin A1c (like in our patient) had 29% lower serum levels of PSA at later stages of diabetes. There have been additional reports on the decrease in testosterone level in men with DM-2 due to hypogonadism evident with low PSA values ( 4 ).…”
Section: Discussionsupporting
confidence: 82%
“…Finally, prostate hyperplasia was found in every third ED patient undergoing CTA. The connection between prostate hyperplasia and ED is quite complex and it was previously reported that 70% of men with prostate hyperplasia have an associated ED [32][33][34]. Thus, our imaging study confirms a close interrelation of prostate hyperplasia and ED.…”
Section: Original Articlesupporting
confidence: 86%
“…Heterogeneity across studies was high (I 2 = 90%, P < 0.001). Six studies (17,19,27,(36)(37)(38) reported scores of assessment tools for sexual dysfunction as a measurement of sexual dysfunction in participants with different severities of LUTS. The result suggested that men with higher severity of LUTS had lower scores of assessment tools for sexual dysfunction compared with those with lower severity (WMD = −5.49, 95%CI: −7.25 to −3.27, P < 0.001, Figure 3).…”
Section: Overall Assessment Of Sexual Dysfunctionmentioning
confidence: 99%
“…In those studies which reported scores of assessment tools for sexual dysfunction, 4 assessment tools had been used to measure sexual dysfunction. Five-item International Index of Erectile Function (IIEF-5), IIEF, Brief Male Sexual Function Inventory (BMSFI) and Epstein Inventory were used to assess sexual dysfunction in two studies (17,37), two studies (19,27), one study (36) and one study (38), respectively. The results showed that participants with higher severity of LUTS had lower scores of the assessment tools than participants with lower severity of LUTS in all groups (IIEF-5 group: WMD = −6.42, 95%CI: −8.26 to −4.58, P < 0.001, I 2 = 92%; IIEF group: WMD = −5.80, 95%CI: −9.70 to −1.91, P = 0.003, I 2 = 37%; BMSFI group: WMD = −2.60, 95%CI: −3.10 to −2.10, P < 0.001; Epstein inventory group: WMD = −5.98, 95%CI: −6.75 to −5.21, P < 0.001).…”
Section: Subgroup Analysismentioning
confidence: 99%